THE RELATIONSHIP BETWEEN PARENTS' OVERPROTECTIVE BEHAVIOR AND STUDENTS' SELF-ADJUSTMENT - Reza Khoirunnisa; Anita; Mustika Suci; Dwi Amalina Putri; Jingga Ramadhona (Journal of Psychology and Social Sciences, 2023)
Problems Children are important members of the family. When children are present in the midst of the family, parents definitely want their children to develop normally, so parents have their own way of treating children. There are also parents who give freedom to children, there are also parents who give freedom to children but still provide control, and there are also parents who indulge in protecting children excessively by providing protection against physical and psychological disturbances and harm, until the child does not reach freedom, the behavior of the parents is called overprotective, with the reason that the child does not experience harm. Many parents intentionally or unintentionally behave over protective. The method used in this study is a qualitative correlation with the data collection technique used, namely a scale questionnaire. The data obtained through the use of questionnaires is data that is classified as factual data. The results of the study based on the line test table 0.01 can be interpreted as significant, because it is smaller than 0.05 and the significant value for the deviation from linearity is 0.052, so it can be interpreted as a significance value greater than 0.05, so from this it can be concluded that the relationship between adjustment variables and parents' overprotective behavior has a linear relationship so that it can also be said that the linearity test is fulfilled in this study.